Elevated serum levels of human epididymis protein 4 in adult patients with proliferative lupus nephritis - Li, Liubing; Xu, Huiya; Le, Yuting; Li, Runzhao; Shi, Qiong; Zhu, Hongji; Xu, Hongxu; Li, Laisheng; Liu, Min; Wang, Fen; Zhang, Hui (Frontiers in Immunology, 2023)
Background: This study aimed to access whether serum human epididymis protein 4 (HE4) level could identify lupus nephritis (LN) pathological classes in adults and children. Methods: The serum HE4 levels of 190 healthy subjects and 182 patients with systemic lupus erythematosus (SLE) (61 adult-onset LN [aLN], 39 childhood-onset LN [cLN], and 82 SLE without LN) were determined using Architect HE4 kits and an Abbott ARCHITECT i2000SR Immunoassay Analyzer. Results: Serum HE4 level was significantly higher in the aLN patients (median, 85.5 pmol/L) than in the patients with cLN (44 pmol/L, P < 0.001) or SLE without LN (37 pmol/L, P < 0.001), or the healthy controls (30 pmol/L, P < 0.001). Multivariate analysis showed that serum HE4 level was independently associated with aLN. Stratified by LN class, serum HE4 level was significantly higher in the patients with proliferative LN (PLN) than in those with non-PLN, and this difference was found only in aLN (median, 98.3 versus 49.3 pmol/L, P = 0.021) but not in cLN. Stratified by activity (A) and chronicity (C) indices, the aLN patients with class IV (A/C) possessed significantly higher serum HE4 levels than those with class IV (A) (median, 195.5 versus 60.8 pmol/L, P = 0.006), and this difference was not seen in the class III aLN or cLN patients. Conclusions: Serum HE4 level is elevated in patients with class IV (A/C) aLN. The role of HE4 in the pathogenesis of chronic lesions of class IV aLN needs further investigation.